БЕРДАҚ ШЫҒАРМАЛАРЫНЫҢ КӨРКЕМ-ЭСТЕТИКАЛЫҚ ДӘРЕКЛЕРИ - Тоқымбетова, Г.А. (FAN va JAMIYAT, 2016)
The article deals with the various aspects of the creative work of the famous Karakalpak poet Berdakh. The author studies ideas and subject matter, genre, literary relations and issues of influence in his works. The influence of the historical situation, literary environment, both folkloristic and aesthetic, and the classics of the East on the formation of the poet‘s lyrics as a genre has also been analyzed.